Case Analysis of Cesarean Scar Pregnancy (CSP) in G3P2A0H2 Gravid at 16-17 Weeks with A History of Two Previous Cesarean Sections - Alhudri, M. Ardaris; Ardiani, Vani; Razali, Renardy Reza (Devotion : Journal of Research and Community Service, 2026)
Cesarean Scar Pregnancy (CSP) is a rare but serious form of ectopic pregnancy with an increasing incidence corresponding to rising cesarean delivery rates. It carries significant risks of massive hemorrhage and uterine rupture. This case report presents a 33-year-old woman (G3P2A0H2) at 16–17 weeks of gestation with two prior cesarean sections, who presented with vaginal spotting. Transvaginal ultrasound revealed a 6.08 × 6.03 cm complex mass in the lower uterine segment consistent with CSP. Initial management with a single-dose methotrexate (50 mg/BSA) regimen was unsuccessful, as bleeding persisted and the mass enlarged to 6.9 × 5.9 cm on follow-up ultrasound. Surgical intervention via CSP resection laparotomy with hysterorrhaphy and Pomeroy bilateral tubectomy was subsequently performed, with an estimated blood loss of approximately 800 cc. The patient recovered well postoperatively, and histopathological examination confirmed the presence of trophoblastic tissue. This case underscores the diagnostic challenges and management complexities associated with advanced CSP. Medical therapy with methotrexate may be ineffective in later gestational stages, necessitating timely surgical intervention to prevent life-threatening complications. Counseling on permanent contraception is essential due to the high recurrence risk. This report highlights the importance of early clinical suspicion, accurate imaging, and multidisciplinary management to optimize outcomes for CSP, particularly in patients with multiple prior cesarean deliveries.